Knowing and Not Knowing ISIS. Issue 1 (2nd January 2019) - Owen, J. Judd
ABSTRACT: Graeme Wood's The Way of the Strangers suggests that many scholars have denied or downplayed the Islamic State's own account of its emphatically religious foundation. This tendency is heir to the Enlightenment strategy of defanging illiberal religion by claiming that only religions conforming to liberal principles are genuinely religious—raising anew questions that arose at the dawn of liberalism, in the wake of the Wars of Religion.